Extreme Mountain Ultra-Marathon Leads to Acute but Transient Increase in Cerebral Water Diffusivity and Plasma Biomarkers Levels Changes - Zanchi, Davide; Viallon, Magalie; Le Goff, Caroline; Millet, Grégoire P.; Giardini, Guido; Croisille, Pierre; Haller, Sven (Frontiers in Physiology, 2017)
Background Pioneer studies demonstrate the impact of extreme sport load on the human brain, leading to threatening conditions for athlete’s health such as cerebral edema. The investigation of brain water diffusivity, allowing the measurement of the intercellular water and the assessment of cerebral edema, can give a great contribution to the investigation of the effects of extreme sports on the brain. We therefore assessed the effect of supra-physiological effort (extreme distance and elevation changes) in mountain ultra-marathons (MUMs) athletes combining for the first time brain magnetic resonance imaging (MRI) and blood parameters. Methods This longitudinal study included 19 volunteers (44.2 ± 9.5 years) finishing a MUM (330km, elevation +24000m). Quantitative measurements of brain diffusion-weighted images (DWI) were performed at 3 time-points: before the race, upon arrival and after 48h. Multiple blood biomarkers were simultaneously investigated. Data analyses included brain apparent diffusion coefficient (ADC) and physiological data comparisons between three time-points. Results The whole brain ADC significantly increased from baseline to arrival (p=0.005) and then significantly decreased at recovery (p=0.005) to lower values than at baseline (p=0.005). While sodium, potassium, calcium and chloride as well as hematocrit (HCT) changed over time, the serum osmolality remained constant. Significant correlations were found between whole brain ADC changes and osmolality (p=0.01), cholesterol (p=0.009), c-reactive protein (p=0.04), sodium (p=0.01) and choline (p=0.002) plasma level variations. Conclusions These results suggest the relative increase of the inter-cellular volume upon arrival, and subsequently its reduction to lower values than at baseline, indicating that even after 48h the brain has not fully recovered to its equilibrium state. Even though serum electrolytes may only indirectly indicate modifications at the brain level due to the blood brain barrier, the results concerning osmolality suggest that body water might directly influence the change in cerebral ADC. These findings establish therefore a direct link between general brain inter-cellular water content and physiological biomarkers modifications produced by extreme sport.